Polyphosphoinositides in the nucleus: Roadmap of their effectors and mechanisms of interaction. (May 2019) - Jacobsen, Rhîan G.; Mazloumi Gavgani, Fatemeh; Edson, Amanda J.; Goris, Marianne; Altankhuyag, Altanchimeg; Lewis, Aurélia E.
Abstract: Biomolecular interactions between proteins and polyphosphoinositides (PPIn) are essential in the regulation of the vast majority of cellular processes. Consequently, alteration of these interactions is implicated in the development of many diseases. PPIn are phosphorylated derivatives of phosphatidylinositol and consist of seven species with different phosphate combinations. PPIn signal by recruiting proteins via canonical domains or short polybasic motifs. Although their actions are predominantly documented on cytoplasmic membranes, six of the seven PPIn are present within the nucleus together with the PPIn kinases, phosphatases and phospholipases that regulate their turnover. Importantly, the contribution of nuclear PPIn in the regulation of nuclear processes has led to an increased recognition of their importance compared to their more accepted cytoplasmic roles. This review summarises our knowledge on the identification and functional characterisation of nuclear PPIn-effector proteins as well as their mode of interactions, which tend to favour polybasic motifs.